Pendampingan Penyusunan Laporan Keuangan Pesantren Di Bangka - sumiyati, sumiyati; Julia, Julia; Aprilian, Rahil Imainul; M. Afdal; Tsulis Amirudin Zahri (Universitas Bangka Belitung, 2024)
Islamic boarding schools are non-profit religious institutions based on education and provide services to the community. However, in financial management, Islamic boarding schools still use simple methods, especially in preparing financial reports. The boarding school applies a single entry system to record its financial transactions. Whereas in accounting, the double entry system facilitates the preparation of financial statements. This activity is a community service programme (PKM) with Islamic boarding schools in Pangkalpinang as partners. Assistance activities for preparing accounting systems and financial reports using the mentoring method. This activity is expected to help Islamic boarding schools prepare financial reports in accordance with applicable accounting standards. The evaluation results were carried out by distributing feedback sheets for target partners to get a picture of how effective this PKM activity was.